Fake : famous forged documents and their historical legacy - O'Sullivan, Donal (McFarland & Company, Inc., Publishers, 2023)
Throughout history, forgers have attempted to fabricate documents to manipulate the historical record. The book explores the most egregious cases - their intent, effectiveness, exposure and significance - from the Donation of Constantine to the Protocols of the Elders of Zion to the Hitler Diaries